2010
DOI: 10.1016/j.jpowsour.2009.12.135
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-reduction activity of silk-derived carbons

Abstract: Carbonized silk fibroin (CS), which is free of metallic elements, showed high catalytic activity for oxygen-reduction reaction (ORR). The catalytic activity of CS for ORR was greatly enhanced by steam activation forming silk-derived activated carbon (CS-AC). The surface morphology, surface area, pore structure and remaining nitrogen species of the CSs were compared with those of the CS-ACs. The open-circuit potential and the power density of a polymer electrolyte fuel cell using a CS900-AC, which was heat-trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 30 publications
1
40
1
1
Order By: Relevance
“…26,27 CS can severe as an effective precursor material to produce carbon catalysts for the ORR. For example, Iwazaki et al successfully prepared activated carbon with high catalytic activity for the ORR via the carbonization and stream-activation of CS; 28,29 however, the steam activation process is relatively complex and timeconsuming. In addition, Wang et al reported CS-derived graphene-like carbon with high catalytic activity for the ORR.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 CS can severe as an effective precursor material to produce carbon catalysts for the ORR. For example, Iwazaki et al successfully prepared activated carbon with high catalytic activity for the ORR via the carbonization and stream-activation of CS; 28,29 however, the steam activation process is relatively complex and timeconsuming. In addition, Wang et al reported CS-derived graphene-like carbon with high catalytic activity for the ORR.…”
Section: Introductionmentioning
confidence: 99%
“…Examples including cotton [7], pollen grains [8], and sawdust [9] have been used as precursors for various carbon based catalysts, and silk [10], pulse flour [11], honey [12], hair [13] and egg white [14] for the preparation of nitrogen-doped ORR catalysts by pyrolysis and post activations. However, the ORR performance of these catalysts in acid [10] or alkaline [11e14] medium remains lower than Pt/C catalysts, and from a practical point of view commercially uncompetitive. Therefore, considerable improvement in ORR catalyst activity is still required from such economical biomass precursors.…”
Section: Introductionmentioning
confidence: 99%
“…Linear Sweep Voltammetry (LSV) Figure 6 shows LSVs of the nitrogen-doped graphene electrocatalyst, at various rotation speeds. It should be noted that very few studies of completely metal-free carbon-nitrogen systems have been performed in acidic conditions [7][8][9][10][11], and only one on nitrogen-doped graphene [28]. Such measurements are generally performed in alkaline solution, where the catalytic activity is well known to be comparable to that of platinum.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…This material was heat treated, and the ORR activity was tested with and without carbon black / multiwall carbon nanotube (MWCNT) supports. The average onset potential in this work was 0.82 V, and the electron transfer number was 3.0 to 3.4, suggesting a mixture of 2-and 4-electron pathways [131 [4][5][6][7][8][9][10][11][12][13][14][15] ]. However, these catalysts were synthesized in a stainless steel vessel, and the supports used may have contained transition metal impurities.…”
Section: Introductionmentioning
confidence: 97%